2020
DOI: 10.1002/kin.21361
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of catalyzed esterification of acetic acid with n‐butanol using carbonized agro‐waste

Abstract: The objective of this research work was to investigate the kinetics of esterification of acetic acid with n-butanol through the variation of experimental parameters. The reaction mixture was catalyzed heterogeneously by a sulfonated catalyst in batch mode of operation. The catalyst was prepared from abundantly available agro-waste, Cajanus cajan husk by chemical activation process, which produces a carbon-based solid catalyst with high surface area. The catalyst was characterized by a Brunauer-Emmet-Teller sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…c ∶ t = c ∶ t (12) in which the value of "c c :c t " could be obtained according to the cis-trans ratio of pinane. Ignoring the error in the cis-trans ratio, when combining Equations (9) and (12), the values of k c and k t could be calculated (Table S3).…”
Section: Linear Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…c ∶ t = c ∶ t (12) in which the value of "c c :c t " could be obtained according to the cis-trans ratio of pinane. Ignoring the error in the cis-trans ratio, when combining Equations (9) and (12), the values of k c and k t could be calculated (Table S3).…”
Section: Linear Methodsmentioning
confidence: 99%
“…Their study reported that the selectivity of cis ‐pinane was more than 96.5%, and the catalyst can be reused eight times. Kinetic research is another effective way to improve the performance of the catalyst because it helps understand the progress of the reaction 12 and theoretically guides the optimization process 13 . Recently, microkinetics has become popular owing to their advantages in complex reaction networks 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Substituting equation 4 into equation 3 and then inverting both sides' results in: (5) In this study, the major Ÿ OH scavengers during ozone-based AOPs in the water matrix are DOM (dissolved organic matters), nitrite (NO2 -) and carbonate/bicarbonate (CO3 2-/HCO3 -). Therefore, the selected wastewater matrix Ÿ OH scavenging rate constant followed equation 5:…”
Section: 1ozone and •Oh Exposurementioning
confidence: 97%
“…Esterification is an important reaction for the production of several chemicals which have significant value in different industries such as pharmaceuticals, solvents plasticizers, etc. [1]. Methyl salicylate is an ingredient of wintergreen and other plants like Amblyomma veriegatum, and it's utilized as a local anesthetic and disinfectant in toothpaste, mouthwash, fragrances, and flavoring agents.…”
Section: Introductionmentioning
confidence: 99%